Sosialisasi Literasi Digital Bermedia Sosial bagi Mahasiswa Untuk Mewujudkan Generasi Bijak Digital - Wardani, Hadidtyo Wisnu; Pria Utama, Gunawan; Saputro, Ari; Hari Prasetyo, Basuki; Christian, Joko Christian (Ikatan Ahli Informatika Indonesia, 2025)
The development of digital technology has made digital literacy an essential skill, especially for young people who are active on social media. The proliferation of hoaxes and invalid information in the digital space requires systematic education on credible and ethical news publishing techniques. This Community Service Activity (PKM) aims to enhance the digital literacy of students participating in the Community Service Learning (KKN) program in Mekarwangi Village, Cisauk, Banten, through training sessions and practical exercises in news publication on social media. The activity is conducted through a combination of lectures and practical exercises, using an educational approach and open discussions. The materials covered ethical behavior on social media, news writing techniques, and strategies for utilizing platforms such as Instagram and Kompasiana, accompanied by concrete examples and interactive dialogue about the participants' experiences. The results of the socialization showed an increase in participants' understanding. An evaluation through a quiz related to the material showed a good level of understanding, with most of the answers being correct. Additionally, the news content published by participants showed significant improvements in writing structure, accuracy of information, and visual appeal. This activity not only provided theoretical insights but also equipped participants with practical skills that can be directly applied in academic and social activities. Thus, this training proved effective in enhancing digital literacy and has the potential to serve as a model for similar educational initiatives in both academic and general community settings